Luoghi del Silenzio Imparziale : Labirinto Contemporaneo - In Labirinto - Bonito Oliva, Achille; Portoghesi, Paolo; Eco, Umberto; Santarcangeli, Paolo; Palazzo della Permanente, Milano (Milano : Giangiacomo Feltrinelli Editore, 1981)
Balla, Giacomo ; Berti, Duccio ; Capogrossi, Giuseppe ; Dali, Salvador ; De Chirico, Giorgio ; Duchamp, Marcel ; Klee, Paul ; Licini, Osvaldo ; Magritte, René ; Merz, Mario ; Miró, Joan ; Mondrian, Piet ; Morris, Robert ; Paolini, Giulio ; Pisani, Vettor ; Pistoletto, Michelangelo ; Pollock, Jackson ; Savinio, Alberto ; Wols
In Labirinto, Palazzo della Permanente, Milano, giugno - agosto 1981
boek